2016
DOI: 10.1055/s-0042-100185
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopist characteristics that influence the quality of colonoscopy

Abstract: This study found that the experience of the endoscopist and exclusive dedication to endoscopy practice, but not annual colonoscopy volume, were associated with better colonoscopy quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 26 publications
2
42
1
Order By: Relevance
“…Practice guidelines recommend post-polypectomy surveillance intervals based on the estimated risk of metachronous neoplasia, which depends on the size, number, and histology of adenomas and serrated lesions found at baseline. [1][2][3] However, adenoma and serrated polyp detection rates, as well as other quality standards, [4][5][6] vary widely among endoscopists, highly influencing the chance of post-colonoscopy cancers, maybe more than the advised interval. 7 Different guidelines on surveillance underscore the need for high-quality baseline colonoscopy before appropriate follow-up recommendations can be made.…”
Section: Introductionmentioning
confidence: 99%
“…Practice guidelines recommend post-polypectomy surveillance intervals based on the estimated risk of metachronous neoplasia, which depends on the size, number, and histology of adenomas and serrated lesions found at baseline. [1][2][3] However, adenoma and serrated polyp detection rates, as well as other quality standards, [4][5][6] vary widely among endoscopists, highly influencing the chance of post-colonoscopy cancers, maybe more than the advised interval. 7 Different guidelines on surveillance underscore the need for high-quality baseline colonoscopy before appropriate follow-up recommendations can be made.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, "younger" endoscopists, public practice setting, low volume of procedures per week and no CRC screening program are items related to more deficiencies. As a recent study has concluded, endoscopic experience, which is commonly reflected by age, volume of procedures per week and participation in a CRC screening program, affects the ADR (38). Our results prove these factors affect ADR but also many of the proposed quality indicators, such as polypectomy under antiplatelets and/or oral anticoagulants therapy, histology and complications feedback, photodocumentation of normal and abnormal findings, use of cleansing scales, complete colonoscopy definition, and use of split dosages.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 For the purposes of this study, endoscopist quality metrics and other demographic characteristics (age, years as physician, years as specialist, exclusive dedication to endoscopy, total lifelong number of colonoscopies, number of colonoscopies the previous year, weekly hours dedicated to endoscopy, and number of formative activities the previous year) were assessed. The ADR was defined as the percentage of colonoscopies performed by each endoscopist in which at least one adenoma was found.…”
Section: Variablesmentioning
confidence: 99%
“…2 On the other hand, colonoscopy quality varies considerably among endoscopists, with important variations in fulfillment of quality indicators, such as adenoma detection rate (ADR) or adenomas per colonoscopy rate (APCR). [4][5][6] This variation suggests that the existence of multiple adenomas in a particular patient depends not only on putative biological factors that would put this patient at risk of developing future lesions but also on the ability of the endoscopist who performs the colonoscopy to detect adenomas. This association gives rise to the paradox that higher-quality baseline colonoscopies would lead to the indication for more surveillance colonoscopies according to current guidelines.…”
Section: Introductionmentioning
confidence: 99%